Assessment of hypoxia avoidance behaviours in a eurythermal fish at two temperatures using a modified shuttlebox system. Issue 1 (17th February 2021) - Ern, Rasmus; Esbaugh, Andrew J.
Abstract: Behavioural avoidance responses of red drum ( Sciaenops ocellatus ) to aquatic hypoxia were investigated at 22 and 30°C using a modified shuttlebox system. Fish movement between a control side maintained at normoxia and a hypoxic side with stepwise decreasing water oxygen tension was analysed for entries into the hypoxic side, residence time per entry into the hypoxic side and total time in the hypoxic side. Acclimation to 30°C increased the oxygen threshold for the onset of hypoxia avoidance behaviours for entries and total time, while residence time per entry was unchanged.